Phrasal Verbs: Their Teaching and Acquisition - Roxana Chevez Herra (Revista de Lenguas Modernas, 2014)
This research study intends to explore the importance of teaching phrasal verbs in the English classroom, as well as to identify the effects that teaching phrasal verbs following an explicit approach has on their acquisition as evidenced by the students’ oral performance. The paper will also point out the importance of engaging students in different systematic classroom activities to be able to determine whether their phrasal verbs acquisition becomes significant and improves their oral performance. Finally, the research intends to understand if there is a correlation between the acquisition of phrasal verbs through explicit and systematic activities used in the classroom, and the students’ performance and proceduralization of phrasal verbs; and if they when presented and studied explicitly in class, can help the students to incorporate them in their oral performance.